STUDI KUALITATIF PENGAMBILAN KEPUTUSAN DALAM KELUARGA TERKAIT DENGAN KOMPLIKASI PERINATAL DI KABUPATEN CIANJUR JAWA BARAT - Melani, Asti (Jurnal Kedokteran Brawijaya, 2008)
ABSTRACT The high number of maternal mortality rate caused by 3 complex problems. One of those problems was delay identification  by  the  family  on  the  risk  factors  of  the  maternal  and  make  decision  in  seeking  help  related  to their problem. The goal of this study was to identify how the family involvement role, especially their husband, to the maternal health and how the decision making pattern in the family, related to the perinatal complication. This  study  is  qualitative  research  using  phenomenology  approach.  The  number  of  participant  in  this  study were six couples husband and wife in Bojongherang, Cianjur, West Java. The findings identified that most of the decision maker in the family were the husbands, except those wife who are the carrier woman. In general, the process of decision making start with discussion from both husband and wife before the decision making is made. Some other is decided by their husband instead. The most influenced factors to the decision making process were socio-economic, accessibility to the health insurance and the family knowledge on the perinatal complications.  The  other  less  influenced  factors  were  gender,  educational  background  and  cultural background.  Key words : Decision making in the family,perinatal complication, maternal health.